Consortia as an Organizational Form of Cooperation in Library and Bibliographic Activities: Foreign Experience - P. V. Prikhozhev (Библиосфера, 2022)
Cooperation at the national and international levels is a promising direction of libraries’ activity. One of the modern forms of such cooperation is library consortia that have been created around the world since the 1960s. The activities of such library associations have been successfully carried out in Russia for many years, but for the more complete understanding of the such organizations’ work character, it is necessary to examine the foreign experience of library consortia creating. Considering the activities of the largest national, regional and international library consortia since the 1960s, one can find out the transformation of such institutions from organizations performing strictly defined functions, such as automating routine library processes or facilitating access to information and exchange of it, into a significant tool for strengthening cooperation in the field of librarianship and bibliography. The article presents the most common definitions of the term «library consortium», defines the main goals and objectives of such organizations, and considers the activities of the largest library consortia of the following types: consortia that unite libraries according to the technological principle and consortia uniting libraries of a certain type. The author pays attention to the International Coalition of Library Consortia (ICOLC), which is a special type of consortium – an association of associations.